2006
DOI: 10.1016/j.bbamcr.2006.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering function and mechanism of calcium-binding proteins from their evolutionary imprints

Abstract: Calcium-binding proteins regulate ion metabolism and vital signalling pathways in all living organisms. Our aim is to rationalize the molecular basis of their function by studying their evolution using computational biology techniques. Phylogenetic analysis is of primary importance for classifying cognate orthologs; profile hidden Markov models (HMM) of individual subfamilies discern functionally relevant sites by conservation probability analysis; and 3-dimensional structures display the integral protein in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…They are expressed by all living organisms, from protists to higher eukaryotes and plants, but with the exception of bacteria. However, the group of Fernandez and Morgan first reported the presence of a gene coding for a single domain annexin in the bacteria Cytophaga hutchinsonii, although the protein is not expressed (Morgan et al, 2006) and a broader survey of bacterial genomes has identified around 30 annexin homologs, including single-domain and multi-domain annexins in 17 bacterial species (Kodavali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed by all living organisms, from protists to higher eukaryotes and plants, but with the exception of bacteria. However, the group of Fernandez and Morgan first reported the presence of a gene coding for a single domain annexin in the bacteria Cytophaga hutchinsonii, although the protein is not expressed (Morgan et al, 2006) and a broader survey of bacterial genomes has identified around 30 annexin homologs, including single-domain and multi-domain annexins in 17 bacterial species (Kodavali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Annexins form a multigene, multifunctional family of amphipathic proteins with a broad taxonomic distribution covering prokaryotes, fungi, protists, plants, and higher vertebrates (Gerke and Moss, 2002;Morgan et al, 2004Morgan et al, , 2006. Found in all plants studied to date and in all organs, these small (32 to 42 kD) proteins can comprise up to 0.1% of total plant cell protein (Delmer and Potikha, 1997;Clark et al, 2001;Moss and Morgan, 2004;Mortimer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an Arabidopsis annexin could be responsible for forming the PM OH _ -activated Ca 2+ conductance. Annexins are membrane binding proteins found in pro-and eukaryotes (Morgan et al, 2006). Several animal annexins have been reported to function in vitro as Ca 2+ channels, including vertebrate annexins A1, 2, 5 to 7, and 12 (Burger et al, 1994;Liemann et al, 1996;Kourie and Wood, 2000).…”
Section: Introductionmentioning
confidence: 99%